Degree modeling of pistachio farmers' resilience against climate change (Study subject: Rural areas of Rafsanjan and Anar counties, Iran) - Asrari, Amirreza; Omidi Najafabadi, Maryam; Farajollah Hosseini, Jamal (Frontiers in sustainable food systems, 2023)
The counties of Rafsanjan and Anar are some of the main production centers of pistachio, an important strategic commodity of Iran that is recently facing major environmental problems such as climate change. Therefore, the present research has modeled the degree of resilience of Rafsanjan pistachio and pomegranate farmers against climate change. The study's statistical population was pistachio farmers in the rural areas of Rafsanjan and Anar, which were 27,860 people. To determine the sample size of the research, a sample size of 588 users was calculated using Cochran's formula, with an error level of 4%. Users were then randomly selected in each village as a proportional assignment. A questionnaire was used for data collection. A group of experts determined its validity, and Cronbach's alpha method was used to determine its reliability and internal consistency. The combined method of Vaikor-entropy was used to measure the resilience behavior of Rafsanjan pistachio and pomegranate farmers against climate change. Data processing was done using MATLAB 7.10, AMOSver24, SPSSver25, and Arc-GIS 10.5 software. The results show that the behavior of the studied farmers' resilience against climate change is at an average level. Also, after analysis, the studied villages were divided into six levels, ranging from lack of endurance to resilient. None of the villages fell into the lowest or highest level. There are 8 villages with a very weak resilience level and 22 villages in the weak resilience level. There are 26 villages at the relatively resistant level and 4 villages in the good resilience level. This finding indicates that the investigated pistachio growers are not in good shape in terms of climate change resilience, and they are unable to deal with larger climate change variations, which can have serious effects on the agricultural sector and the villages' livelihoods.